Community Perceptions of Mangrove Ecotourism in Jeflio Village, Mayamuk District - Manurung, Melani; Yanti, Dwi Indah Widya; Payung, Clara N; Wantah, Felia K.T.Y (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
The existence of mangrove forests around Jeflio Beach, Mayamuk District, Sorong Regency, ecologically will affect the biodiversity of coastal natural resources and socio-economically will have an impact on the growth of business income of the community around the area. The purpose of this study is to determine the public’s perception of the existence of mangrove ecotourism objects in Jeflio Village, Mayamuk District, Sorong Regency. This study uses a qualitative descriptive analysis. The data in this study are primary data and secondary data obtained by means of observation and interviews. The community’s and increases people’s income. There is an influence in terms of the existence of ecotourism and the level of income on the characteristics of the community.